Diagnostic Utility and Psychometric Properties of the Beck Depression Inventory-II Among Korean Adults - Park, Kiho; Jaekal, Eunju; Yoon, Seowon; Lee, Seung-Hwan; Choi, Kee-Hong (Frontiers in Psychology, 2020)
The Beck Depression Inventory-II (BDI-II) is one of the most widely used depression assessment tools in Korea. However, the psychometric properties and diagnostic cut-off point of the official Korean version of the BDI-II have not yet been reported. This study aims to clarify the psychometric properties and diagnostic utility of the Korean BDI-II. A total of 1,145 clinical and nonclinical Korean adults participated in the study. The BDI-II showed a high level of internal consistency, and the correlations between the BDI-II and other depression-related measures were high. Confirmatory factor analysis was performed, and a 3-factor model showed the best model fit. To identify the diagnostic utility of BDI-II, the Quality Assessment of Diagnostic Accuracy Studies 2nd Edition (QUADAS-2) methodology was applied in participant recruitment and research design. Results of ROC curve analysis suggested two optimal cut-off scores, 23 points for detecting major depressive disorder (83.3% sensitivity, 86.8% specificity) and 17 points for depressive-related disorder (80.9% sensitivity, 76.4% specificity). To identify the usefulness of the BDI-II as a severity assessment tool or screening tool, a test information curve was generated with an Item Response Theory analysis The test information curve showed a flat, plateau-like line, indicating a good profile as a severity rating tool. Research data support the BDI-II as a reliable and valid screening tool as well as a severity measurement tool in the Korean adult population.